Multicenter Selective Lymphadenectomy Trial‐I confirms the central role of sentinel node biopsy in contemporary melanoma management Response to 'No survival benefit for patients with melanoma undergoing sentinel lymph node biopsy: critical appraisal of the Multicenter Selective Lymphadenectomy Trial‐I final report'. (1st March 2015) - Faries, M.B.; Cochran, A.J.; Elashoff, R.M.; Thompson, J.F.
Summary: Sentinel lymph node (SLN) biopsy has become a standard procedure for many patients with melanoma and is recommended in numerous national and professional melanoma guidelines. The Multicenter Selective Lymphadenectomy Trial (MSLT‐1) confirms earlier large database studies and prospective clinical trials in demonstrating the independent and unequalled prognostic value of the SLN. It also demonstrates the ability of biopsy‐directed management to provide effective regional disease control with the least possible morbidity. These benefits are not in question and provide ample justification for the procedure, even without evidence of a survival benefit. However, MSLT‐1 also provides strong evidence of a substantial reduction in the risk of melanoma death for patients with intermediate thickness melanomas who harbour occult nodal metastases at the time of presentation. Denying appropriately selected patients with melanoma the opportunity to undergo SLN biopsy is no longer reasonable or acceptable.